Analysis of personal competences in teachers: a systematic review - Molina-Moreno, Pablo; Molero-Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Gázquez-Linares, José Jesús (Frontiers in Education, 2024)
The relevance of teachers' emotional and social competencies in education has been highlighted as they enable them to establish effective relationships, manage emotional situations and create positive learning environments. The absence of these competencies can lead to emotional exhaustion and negatively affect the classroom environment, thus stressing the need to strengthen these skills so that teaching professionals can adapt to the changing demands of the educational environment.Objective: The primary aim of this paper is to analyze the existing programs for training socioemotional skills in teachers and evaluate their effectiveness. To achieve this, a systematic review of the literature is conducted, focusing on the empirical research existing to date that promotes and enhances these skills through intervention programs.Methods: A literature search was performed using the electronic databases Psycinfo, Psicodoc, Psychology Database, Pubmed, Sicence Direct and Dialnet Plus, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were eligible for inclusion in this review if they investigated the effectiveness of interventions and training protocols for enhancing personal competencies of a sample of participants composed of teachers.Results: Activities aimed at strengthening personal competencies in teachers tend to have a positive impact on areas such as job satisfaction, professional commitment, emotional management, and stress reduction, which has a favorable impact on students. However, the effectiveness of these interventions may vary depending on the design of the study and the individual characteristics of the participants.The importance of training educators in personal and emotional skills is highlighted, due to its feasibility and the benefits it implies for both educators and students. Valuable insights for future practices, emphasizing the need for continuous training, digital technologies, mentoring, and holistic well-being to improve educational quality and job satisfaction for teachers are provided.